COMPARISON OF MEASUREMENT SHAFT DISPLACEMENT, BEARING CASING VIBRATIONS AND AXIAL FORCES IN THREE DIFFERENT KAPLAN TURBINES - Boštjan Gregorc; Andrej Predin (Journal of Energy Technology, 2024)
This paper deals with the vibrations and displacements of turbines haf tsat different aggregateloads in hydroelectric power stations. Measurements have been made atthree different power plant swith Kaplan turbines.Thefirst part contains the oretical starting points for the evaluationof the measurement signals of displacements and of vibrations. The results of the evaluation measurements are show nint heexp erimental part accompanied by comments.The findings of the treated results of measurement are introduced.